2021
DOI: 10.1080/10942912.2021.1953070
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical properties of purple cabbage as affected by drying conditions

Abstract: This work aimed to investigate the effect of five drying methods, namely hotair drying (HD), microwave drying (MD), vacuum drying (VD), vacuum microwave drying (VMD), and vacuum freeze-drying (VFD), on the bioactive compounds, antioxidant activity, color, sensory attributes, and microstructure of purple cabbage. Different drying methods considerably affected the quality factors of the products. The highest remaining total phenolic content (TPC), total flavonoid content (TFC), and total anthocyanin content (TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Studies have been reported on similar raw materials, such as Chinese cabbage, that were dehydrated by different methods such as oven drying, solar cabinet drying, sun drying, and freeze drying, showing a greater impact on phenolic compounds [ 31 ]. Studies on red cabbage dehydrated by hot air drying, microwave drying, vacuum drying, vacuum microwave drying and vacuum freeze drying have concluded that freeze drying maintains the content of phenolic compounds better [ 32 ]. However, this methodology involves greater energy consumption, increasing costs, and has a greater environmental impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been reported on similar raw materials, such as Chinese cabbage, that were dehydrated by different methods such as oven drying, solar cabinet drying, sun drying, and freeze drying, showing a greater impact on phenolic compounds [ 31 ]. Studies on red cabbage dehydrated by hot air drying, microwave drying, vacuum drying, vacuum microwave drying and vacuum freeze drying have concluded that freeze drying maintains the content of phenolic compounds better [ 32 ]. However, this methodology involves greater energy consumption, increasing costs, and has a greater environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…However, this methodology involves greater energy consumption, increasing costs, and has a greater environmental impact. There are few works on the dehydration of red cabbage; however, existing studies primarily focus on assessing its nutritional content, particularly anthocyanins and physical properties, and the most common drying techniques explored include hot air-, vacuum- and microwave drying [ 32 , 33 , 34 ], but there is still a need for further research on the impact of different drying methods on the retention of specific bioactive compounds and their potential health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to quality prospectus, concerns that producers are preoccupied with are energy usage that influences drying costs. These concerns may be reduced by microwave-assisted hot air drying (Poogungploy et al, 2018;Kaveh et al, 2021;Yue et al, 2021).…”
Section: Introductionmentioning
confidence: 99%